USM VICE-CHANCELLOR RECEIVES COURTESY CALL FROM NEW JAPANESE CONSUL-GENERAL - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 31 May 2016 – The ViceChancellor of Universiti Sains Malaysia (USM), Professor Dato’ Dr. Omar Osman recently received a courtesy call from the new Japanese ConsulGeneral in Penang, Kiyoshi Itoi.